ATOM TRANSFER RADİKAL POLİMERİZASYONUYLA T-BÜTİL METAKRİLAT’IN METİL METAKRİLAT İLE ÜÇ KOLLU YILDIZ KOPOLİMER SENTEZİ VE KARAKTERİZASYONU - GÜNGÖR, TUĞBA (Fırat Üniveristesi, 2006)
Tersiyer bütilmetakrilat (t-BMA) homopolimeri ve metilmetakrilat (MMA), etilmetakrilat (EMA) ve n-bütilmetakrilat (n-BMA) ile etilmetakrilatın (EMA) bir seri üç kollu yıldızkopolimer sentezinde başlatıcı olarak 1,3,5-(2-Bromo-2-metelpropiyonato)benzen, katalizörosistem olarak Cu(I)Br/2,2'-bipiridin kullanılarak 110 C de Atom Transfer RadikalPolimerizasyon (ATRP) metodu kullanıldı. Homo ve kopolimerler FT-IR, 1H-NMR teknikleriylekarakterize edildi. Kopolimer bileşimleri 1H-NMR spektrumlarından hesaplandı. Molekül ağırlığıve molekül ağırlığı dağılımı Jel Geçirgenlik Kromatografisi (GPC) ile elde edildi.Kopolimerizasyon sistemde Kelen-Tüdös ve Finemann-Ross metodlarıyla monomer reaktiviteoranları hesaplandı. Üç kollu t-BMA'ın homo- ve MMA, EMA ile kopolmerleri ve üç kollu poli(n-BMA-EMA) kopolimerlerinin termogravimerik analiz (TGA) ölçümleriyle termal kararlılıklarıölçüldü. Üç kollu poli(t-BMA-ko-MMA), poli(t-BMA-ko-EMA) ve poli(n-BMA-ko-EMA) ıncamsı geçiş sıcaklıkları (Tg) Differensiyel Scanning Kalorimetri (DSC) ile ölçüldü,. Tgkopolimer bileşiminin bir fonksiyonu olarak grafiğe geçirildi. Elde edilen sonuçlar karşılaştırıldı.Anahtar Kelimeler: ATRP, üç kollu polimer, sentez, monomer reaktivite oranı.

1,3,5-(2-Bromo-2-methylpropionato)benzene was used as a three functional initiator inthe synthesis of three-armed star polymer of t-butylmethacrylate (t-BMA) and their copolymerswith methylmethacrylate (MMA), ethylmethacrylate (EMA) and n-butylmethacrylate (n-BMA)with ethylmethacrylate (EMA) via the atom transfer radical polymerization (ATRP) method inpresence of Cu(I)Br/2,2-bipyridine catalitic system at 110 oC. The homo- and copolymers werecharacterized by FT-IR, 1H-NMR techniques. The compositions of the copolymers werecalculated from 1H-NMR spectra. The molecular weight and molecular weight distribution wereobtained by Gel Permeation Chromatography (GPC). For copolymerization system, theirmonomer reactivity ratios were obtained by using Kelen-Tüdös and Fineman-Ross methods. Thethermal behavior of three-armed homopolymer of t-BMA and its copolymers with MMA andEMA, and three-armed poly(n-BMA-co-EMA) were studied by thermogravimetric analysis(TGA). The glass transition temperature (Tg) of three-armed poy(t-BMA-co-EMA) and three-armed poy(t-BMA-co-EMA) and three-armed poy(n-BMA-co-EMA) were measured ydifferential scanning calorimetry (DSC). Tg as a function of copolymer composition was plotted.The results obtained were given in comparison with each other.Keywords: ATRP, three-armed polymer, synthesis, monomer reactivity ratios.
Three armed star polymer synthesis and characterization of methylmethacylate with t-butylmethacrylate via atom transfer radical polymerization method
Keywords: Kimya